Malaria-derived hemozoin skews dendritic cell responses to bacterial infections by reducing interferon gene-transcription by SWI/SNF-NuRD - Gintare Lasaviciute; Kanwal Tariq; Anaswara Sugathan; Jaclyn Quin; Mareike Polenkowski; Ioana Bujila; Oleksii Skorokhod; Marita Troye-Blomberg; Eva Sverremark-Ekström; Ann-Kristin Östlund Farrants (iScience)
Summary: Hemozoin (HZ), the malaria pigment, is associated with the disease when released during the pro-inflammatory blood stage and co-infections with bacteria lead to a more severe disease progression. The underlying mechanisms are poorly understood and, here, we show that the impact of co-exposure to HZ and lipopolysaccharide (LPS) on monocyte-derived dendritic cells (moDC) alters the early transcriptional response to a subset of IFNγ controlled genes, HLA-DR, and PD-L1. HZ-exposure had no effect on inflammatory genes, which were substantially induced by LPS. The reduced expression of HLA-DR and PD-L1 by HZ was associated with the chromatin remodeling complex NuRD and a decreased binding of the NF-κB transcription factor RELA compared to cells stimulated with LPS alone. NuRD replaced the SWI/SNF complex variant PBAF at the specific promoters, without chromatin accessibility changes. The immune modulatory effect of HZ may lead to changed immune responses to bacterial co-infections.